Hotel promotion using push-based technology - W. Zakira, Wan Mohd Najib (2010)
Hotel Promotion Using Push-based Technology (HPUPT) is a promotion about hotel that uses the Push-based Technology. In this hotel promotion case, Simple Messaging System (SMS) will be sending as the advertisement to attract the customers' attention to know the details of the promotion. HPUPT system will introduce a new way of advertisement technique from emailing system to the most popular communication equipment, mobile technology. This system also provides ease of use and flexibility to the administrator to do promotion about the hotel through mobile application as administrator can edit and update the advertisement at anytime. In order to make sure that the development of the project can be conduct in a smooth way, System Development Life Cycle (SDLC) method is selected. The Systems Development Life Cycle (SDLC) is the process of creating or altering systems, and the models and methodologies that used to develop the systems. The entire interface for Hotel Promotion Using Push-based Technology (HPUPT) system will be designed to be as friendly as possible. All the details about the promotion should be simple but compact and clear enough for customers to understand and get enough information about the promotion.